Analysis of The Transformation of The District Economic System in Riau Province - Desi Damaiyanti; Harlen Harlen; Any Widayatsari (Westscience Press, 2024)
This research aims to look at the economic structure transformation in each district in Riau Province. The method used is analyzing competitive advantage and specialization of Esteban Marquillass and Klassen typology. From the results of processing, it is known that agriculture, forestry, and fisheries are superior sectors, have competitiveness, and are specialized in 6 districts in Riau, namely Indragiri Hulu (Inhu), Kampar, Indragiri Hilir (Inhil), Pelalawan, Kuantan Singingi (Kuansing), and Rokan Hulu (Rohul). The manufacturing industry is a superior sector that has competitiveness and specialization in Dumai City, and the trade sector is a sector that has a competitive advantage and specialization in Pekanbaru City. Meanwhile, no single industry has a competitive advantage and specialization in 4 other districts (Siak, Bengkalis, Rokan Hilir, and Kepulauan Meranti). Processing results with the Klassen typology show that the agricultural industry in Kuansing, Inhu, and Kampar Regencies, which 2012 was developing, will shift to become a mainstay sector in 2022. In contrast, in Bengkalis, Pekanbaru, and Dumai Regencies, this sector is still one of the lagging economic sectors.